Iron product available for cooking
A zirconium oxide and alkali silicate coating system on iron utensils addresses sticking and rust issues, ensuring pattern durability and ease of cleaning under high-temperature cooking conditions.
Patent Information
- Application Number
- JP2023204360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-08
- Filing Date
- 2023-12-04
- Publication Date
- 2024-12-19
AI Technical Summary
Existing iron cooking utensils face issues with food sticking, rust prevention, and pattern durability under high-temperature cooking conditions, as conventional coatings like fluororesin, silicone resin, and silica films fail to withstand high heat and boiling water.
A two-layer coating system comprising a zirconium oxide layer followed by a transparent alkali silicate layer containing lithium is applied to the iron surface, protecting the oxidation-induced patterns and enhancing resistance to thermal shock, boiling water, and rust.
The coating system maintains pattern clarity and prevents rust, reduces food sticking, and facilitates easy cleaning, allowing for long-term use at high temperatures exceeding 300°C.
Smart Images

Figure 2024177033000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to iron products that can be used for cooking. More specifically, the present invention relates to iron products that can be used for cooking, and that can be colored in red, brown, blue, purple, black, and other colors due to the oxidation of iron, and that retain their coloring for a long period of time even under harsh conditions such as cooking at high temperatures of about 300°C and in boiling water, and that are resistant to rust, difficult to stick to food ingredients, and easy to clean. [Background technology]
[0002] Iron products are widely used as cooking utensils for heating, such as iron plates, frying pans, and pots. Although uncoated solid products have the disadvantages of food sticking to them and the difficulty of rust prevention, they are in strong demand because they can be used for cooking at high temperatures exceeding 300°C. On the other hand, due to the increasing need for design in kitchen products, there is an increasing demand for various colors and patterns on the cooking surface inside as well as the outside. For example, a frying pan coated with fluororesin can be easily colored by using a pigment, but the upper limit temperature of this fluororesin coating is 260°C, which is lower than that of solid iron products, so it is difficult to cook on high heat. Glass materials containing pigments such as enamel are heat resistant, but the film thickness is thick and they are vulnerable to thermal shock, so they are ultimately not suitable for high heat cooking. Therefore, as a method of coloring without using pigments and binders to fix them, it is possible to use the fact that iron products oxidize when heated and turn black, blue, brown, purple, yellow, etc., and create patterns by contrasting them with the original silver part that is not colored.
[0003] However, to achieve this, it is necessary to protect the pattern from the harsh conditions of cooking, which include high temperatures, boiling water, salt, acid, and alkali. Moreover, if the pattern is to be protected by a coating, it must be transparent in addition to its protective function, which is an extremely difficult problem. For example, inorganic silica-based coatings can withstand high temperatures, but they dissolve easily in boiling water, which causes the problem of disappearing after a few uses.
[0004] Also, you can often see iron cookware coated with silicone resin, but this is for the purpose of preventing rust from the time of manufacture until the time of actual use, and as this will disappear after a few cooking uses, although it may be able to protect the color for a short period of time, it is not suitable for long-term use.
[0005] There are no prior art documents that specifically aim to protect the coloring of cookware by utilizing the oxidation of iron, but there are some prior art documents that protect iron with inorganic substances to prevent rust. The current commercially available technologies for treating iron frying pans with the aforementioned silicone resin and silica are explained in Non-Patent Documents 1 and 2, respectively.
[0006] On the other hand, Patent Document 1 describes a rust prevention technology in which an alkaline aqueous solution of zirconium carbonate is applied to the metal surface. Patent Document 2 also discloses a method in which rust prevention is not sufficient only with an alkaline aqueous solution of zirconium carbonate, and a silicon compound is added to an ammonium salt solution of zirconium carbonate, and the resulting solution is further covered with the silicon compound. The zirconium compound in Patent Document 1 is heated to become zirconium oxide, but as Patent Document 2 shows, this zirconium oxide layer alone is insufficient in terms of rust prevention performance. However, even with the method in Patent Document 2, although rust prevention can be ensured, there is a problem in that the boiling water resistance required for cooking is insufficient. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication 50-144639 [Patent Document 2] Patent Publication No. 2009-41077 [Non-patent literature]
[0008] [Non-Patent Document 1] https: / / www.wahei.co.jp / reading / trivia / 144.html [Non-Patent Document 2] https: / / www.nitori-net.jp / ec / product / 8943613s / Summary of the Invention [Problem to be solved by the invention]
[0009] The object of the present invention is to provide an iron product that can be used for cooking and can be colored. The meaning of being usable for cooking is that it can withstand not only high temperatures of about 300°C, which is higher than the upper limit of fluororesin, but also harsh conditions such as not disappearing even when exposed to boiling water, like silicone resin or silica films. More specifically, the object of the present invention is to provide an iron product that utilizes the coloring phenomenon caused by the oxidation of iron to draw patterns, and protects the coloring with a transparent coating layer, so that the patterns do not disappear for a long time even when used for cooking. Another object of the present invention is that, regardless of whether or not there is coloring due to oxidation, this transparent coating layer has an anti-rust effect, does not easily stick to food, and is easy to clean. [Means for solving the problem]
[0010] In the present invention, the above-mentioned problem is solved by coating the iron surface with a zirconium oxide layer, and then coating the zirconium oxide layer with a layer containing silicic acid, preferably a transparent alkali silicate layer containing lithium. However, if the iron surface is not smooth or in order to control coloring due to oxidation as described below, the iron surface may be coated with an alkali silicate layer before coating with the zirconium oxide layer. It was also found that further coating the outermost alkali silicate layer with a zirconium oxide layer makes food less likely to stick, and this invention was able to be completed more. In addition, this iron product that can be used for cooking can be provided with a pattern design with or without colored parts by coloring the entire or part of the surface by oxidation before forming the first zirconium oxide layer. This colored or uncolored part is protected by a coating layer that is provided later, so it can withstand long-term use. Effect of the Invention
[0011] This invention has made it possible to obtain iron products that can be used for cooking and can also be colored to create patterns. These utilize coloring caused by the oxidation of iron, and unlike conventional products that use fluorine, silicone resin, or silica, they are excellent in heat resistance, thermal shock resistance, and boiling water resistance, and can be used in the same way as solid iron products. Moreover, they are less susceptible to rust than solid iron products. They can be used for frying pans, iron plates, pots, etc. [Brief description of the drawings]
[0012] [Figure 1] Fig. 1 is a schematic diagram of the present invention, in which a part of an iron plate (100) is colored by oxidation (120), and the iron plate and the colored part by oxidation are covered with a transparent lithium-containing alkali silicate layer (110) as required. This is further protected by two layers, a zirconium oxide layer (130) and a transparent lithium-containing alkali silicate layer (140). [Diagram 2] FIG. 2 is a schematic diagram of the present invention, in which the substrate of FIG. 1 has been further coated with a transparent zirconium oxide layer (250). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In carrying out the present invention, it is preferable to provide a portion on the iron surface that is colored by oxidation reaction and a portion that is not oxidized and colored, and then color or draw a pattern on the portion. A representative example of coloring by oxidation reaction is black skin that occurs by heating, and coloring that shows gold, purple, blue, and black due to the formation of iron oxide called black rust. This coloring also shows a corrosion prevention effect, so it is suitable for the present invention. Although coloring by red rust is also possible, this does not show a corrosion prevention effect, but since iron cookware may be expected to have a nutritional iron supply function, it cannot be said that it is not suitable in general. There are various other coloring methods by oxidation reaction, but the type of coloring method is not particularly limited in the present invention. On the other hand, the portion that is not colored by oxidation is the surface of the iron itself without the oxide layer formed, and shows a silver color. The ratio of the colored and non-colored portions is not particularly limited because it depends on the design. For example, a design consisting of black and blue with different degrees of oxidation is also acceptable, and does not necessarily mean that silver portions are required. Conversely, a design with only silver color is not inconvenient. When drawing designs, it is possible to expose the original silver color by polishing or etching the colored parts, or to control the degree of oxidation by masking. It is also possible to utilize changes in color due to temperature differences. As described above, there are various methods for drawing designs, but the present invention does not limit the drawing method in particular.
[0014] This colored or drawn pattern needs to be protected. Since the present invention is aimed at iron products that can be used for cooking at high temperatures, a protective coating such as fluororesin that can only be used for cooking at 260°C or less is not suitable. In addition, a protective coating such as silicone containing silicon or silica that can be used at high temperatures of about 300°C but disappears when it comes into contact with boiling water is not suitable. Therefore, in the present invention, it was considered to cover the pattern with a transparent zirconium oxide layer that does not contain silicon. This is because the problem of reduced boiling water resistance occurs when silicon is included. This is not only because the boiling water resistance of the silicon compound itself is low, but also because the zirconium component and the silicon component react chemically in the coating liquid to gel, so that even if it can be applied, it is considered that the structure will be weak. Therefore, it is preferable that this zirconium oxide layer is made of zirconium oxide alone as much as possible, and it is not preferable to add components other than silicon. Even if it is unavoidable, it is preferable that other components such as impurities are 10% or less. If the coating is not transparent, the pattern cannot be seen, and from this point of view, it is also not preferable to add impurities.
[0015] However, there are cases where this zirconium oxide layer not containing silicon cannot be successfully formed. This is particularly noticeable when the iron substrate is porous or has a large surface roughness, such as in the case of a cast iron. Even if a coating liquid for forming zirconium oxide is applied to such a substrate, the liquid is absorbed, and the film may not be successfully formed. In addition, there are cases where it is desired to change the color tone or gloss for design reasons. In such cases, the pores can be sealed or smoothed in advance with a glass material containing silicon before applying the coating liquid for zirconium oxide. Specifically, glass materials such as enamel and water glass can be used. Although the hot water resistance of such glass materials is not very good, there is no problem because it penetrates into the pores and is covered with a zirconium oxide layer that has excellent hot water resistance. The thickness of this is preferably about the extent that the pores are sealed.
[0016] Although it is possible to protect the iron surface to some extent with a layer made of zirconium oxide, it is not sufficient to protect the iron surface from discoloration caused by high-temperature heating during cooking of the pattern. To prevent this discoloration, it is preferable to further cover the zirconia oxide layer with a transparent layer containing silicon. This two-layer structure is different from the above-mentioned mixture in that it is contact at the interface, so there is no gelation reaction in the coating liquid and no weakening of the film structure. On the contrary, since the reaction between the zirconium component and the silicon component occurs at the interface, the adhesion of both layers is improved, and the boiling water resistance of the silicon-containing layer is also improved compared to when it is in direct contact with the iron surface. Even in such a two-layer structure, if the silicon component is mixed into the first layer coating liquid, the zirconia component will first react with the silicon component in the mixed liquid and its activity will decrease, so that there will be less room for reaction with the silicon component of the second layer. For this reason, it is not preferable for the coating liquid that forms the first layer of zirconium oxide to contain a silicon component.
[0017] The transparent silicon-containing layer is preferably an alkali silicate containing lithium, since it can prevent discoloration and improve boiling water resistance.It is well known that an alkali silicate layer containing lithium has improved water resistance compared to a layer that does not contain lithium, but when it is applied to a zirconium oxide layer that does not contain silicon, not only water resistance but also boiling water resistance is further improved.As mentioned above, if the zirconium oxide layer does not contain silicon, it can react and bond with the silicon component that is further laminated, which is thought to be a synergistic effect with the water resistance improvement effect of lithium, and the boiling water resistance effect is further strengthened.
[0018] If this lithium-containing alkaline silicate layer is covered with a silicon-free zirconium oxide layer, not only is hot water resistance improved, but food sticking is also reduced. The reason for the improved hot water resistance is the same as above, but the reason for the reduced sticking is thought to be that the surface of zirconium oxide is more inactive than that of silicate.
[0019] The method of manufacturing the present invention involves first coloring the iron surface. For this, it is preferable to use the oxidation reaction of iron, and a method of mixing pigments and dyes with a binder and painting is not preferable because it limits high-temperature cooking, which is an advantage of iron cookware. As a coloring method by oxidation, a method using heat is preferable because it can be done easily, but there is also a method using chemicals, and there is no particular limit to these. To create a pattern, it is possible to use a method of polishing or engraving the oxidized part to expose the part that is not to be colored, a method of masking the part that is not to be colored before oxidation, or a method of masking the exposed part after oxidation coloring and decolorizing it. It is also possible to change the shade of the pattern by the degree of oxidation and polishing, or the degree of covering with a masking material, etc. Any design can be used, and there is no limit to the degree of oxidation.
[0020] The manufacturing method of the iron product of the present invention that can be used for cooking is characterized in that the surface colored by oxidation is coated with a coating liquid that forms zirconium oxide. For this purpose, it is preferable to coat the surface with an aqueous solution of ammonium zirconium carbonate by coating and drying. Ammonium zirconium carbonate becomes zirconium oxide in a subsequent heating process. Ammonium zirconium carbonate is an inorganic substance represented by the chemical formula (NH4)2[Zr(CO3)2(OH)2], and can be made into a coating liquid by diluting it with water. It is preferable to exclude additives as much as possible, except for water and surfactants that are unavoidably added for making paint. In particular, the addition of silicon compounds not only promotes the gelation of the coating liquid, making it difficult to paint, but also causes a decrease in the hot water resistance of the coating film and a decrease in the adhesion of the silicon compounds described below, so it is not recommended to add silicon compounds. It is preferable not to add any impurities. It is also preferable to avoid mixing impurities unless it is unavoidable. The concentration of the coating solution is 1 to 10%, and the coating amount is preferably 10 to 2000 mg / m2 in terms of zirconium oxide, more preferably 100 to 2000 mg / m2. If the amount is too small, the protective effect is weakened, and if it is too thick, there is a high risk of the coating film peeling off. There is no particular limit to the coating method, and spraying, brush coating, dipping, and roller coating are possible. After coating, the coating is dried. Drying is preferably done naturally or at 300°C or less. If the temperature exceeds 300°C, there is a risk that the adhesion with the silicon-containing layer described below will decrease.
[0021] If the iron substrate is a cast iron and is porous or has a large surface roughness, the coating liquid forming the zirconium oxide may be absorbed and the surface may not be covered properly. In such cases, it is preferable to cover the porous or rough surface with a silicon-containing glass material in advance to prevent absorption. As this glass material, it is convenient and preferable to apply so-called water glass (lithium silicate, sodium silicate, potassium silicate). It is also possible to use a glaze such as enamel. Such glass materials can also be used to give a gloss to the surface for design purposes, or as a mask for coloring due to oxidation.
[0022] The protective effect of zirconium oxide alone is insufficient in terms of heat discoloration resistance, and when used as a cooking utensil for a long period of time, oxidation progresses and the pattern tends to become difficult to see. To prevent this, it is preferable to further coat the coating layer, which is formed by applying and drying the above-mentioned ammonium zirconium carbonate aqueous solution, with an aqueous solution of alkali silicate containing lithium, and then heat and dry it. This heating is preferably performed at 200°C or higher, more preferably 250°C or higher. After this, ammonia and water are released from the ammonium zirconium carbonate by heating, and the zirconium oxide is converted into zirconium oxide, and at the same time, this is closely attached to the layer of alkali silicate containing lithium, thereby improving both heat discoloration resistance and hot water resistance at the same time.
[0023] A coating layer containing silicon such as silicone or silica is suitable for preventing thermal discoloration of a pattern due to oxidation of iron at high temperatures because of its low oxygen permeability. However, this coating layer has low hot water resistance, so it dissolves in applications where it comes into contact with hot water, such as cooking utensils, and discoloration cannot be prevented for a long period of time. It is well known that lithium silicate has excellent water resistance as a silicon compound that can be used as a coating layer, but this is also insufficient in terms of hot water resistance such as boiling water. However, as in the present invention, when it is brought into contact with the zirconium ammonium carbonate layer by coating rather than mixing, a chemical reaction occurs at the interface, improving adhesion, and there is an advantage that the hot water resistance and heat discoloration resistance are improved simultaneously. If the two are mixed rather than in contact, a chemical reaction proceeds in the coating liquid at the same time as mixing, so it is presumed that sufficient hot water resistance and heat discoloration resistance cannot be obtained. The preferred range of solid content of the coating liquid is SiO2=70-90wt%, Li2O=1-5wt%, and Na2O+K2O=5-29wt%. The coating liquid is an aqueous solution with a solid content of 1 to 20 wt%, and it is preferable to add a surfactant from the viewpoint of coating properties. There is no particular restriction on the surfactant. The coating amount is 10 to 3000 mg / m2, more preferably 100 to 2000 mg / m2, calculated as SiO2. If it is too thin, the effect is insufficient, and if it is too thick, there is a risk of peeling. As the aqueous alkali silicate solution containing lithium, it is convenient and preferable to use an aqueous alkali silicate solution such as commercially available lithium silicate, sodium silicate, or potassium silicate. There is no particular restriction on the coating method, and spraying, brush coating, dipping, roller coating, etc. can be applied. Heating is preferably at 250°C or higher so that zirconium oxide is generated. There is no particular upper limit, but it is preferable to use 500°C or lower at which the iron plate does not deform.
[0024] So far, the effects of the two layers, the zirconium oxide layer and the alkali silicate layer, have been described, but it has been found that if these two layers are further coated with a zirconium oxide layer, the adhesiveness of the food during cooking is further improved, making maintenance easier and protecting the alkali silicate layer from dissolution by boiling water, which is one of the objects of the present invention. The lamination method of the third layer is preferably performed after the coating and drying of the second layer, and after coating, it is preferable to heat to 200°C or more, more preferably 250°C or more. The third zirconium oxide layer is preferably coated in the same manner as the first zirconium oxide layer. EXAMPLES
[0025] The present invention will be described in detail with reference to examples, but the present invention is not limited to these examples. "Examples 1 to 5" "Comparative Examples 1 to 2" Here, we investigated the protection of the pattern when the amount of ZrO2 applied was changed stepwise while the amount of SiO2 applied was fixed. A 10cm x 10cm iron plate was heated in an oven at 300°C for 60 minutes to color it bluish black. The surface of this iron plate was scraped with a file to create a silver pattern. The scraped parts will be the original silver color of the iron plate, so a silver pattern is drawn against a black background. The ratio of scraped parts is arbitrary. Ammonium zirconium carbonate (product of Nippon Light Metals, ZrO2 equivalent content 20wt%) was diluted with distilled water to prepare coating solutions with ZrO2 = 0, 0.1, 1.0, 5, 10, and 20wt%. 0.1g of each coating solution was dropped onto the iron plate surface (area 0.01m2) and spread evenly over the entire surface. The coating amount ratios, in terms of ZrO2, were 0, 10, 100, 500, 1000, and 2000mg / m2, respectively. For 3000mg / m2, 0.3g of 10% solution was dropped. This was dried at 100°C for 5 minutes. Next, an aqueous solution of an alkali silicate containing lithium with a composition of SiO2=10wt%, Li2O=0.3wt%, Na2O=1.7wt% (solid composition SiO2=83.3wt%, Li2O=2.5wt%, Na2O=14.2wt%) was prepared, and 0.1g of the solution was dropped onto the iron plate coated with the ammonium zirconium carbonate and spread evenly over the entire surface. The coating amount ratio of this is 1000mg / m2 in terms of SiO2. This was heated in an oven at 300°C for 60 minutes. After observing the appearance after heating, those that had no abnormal appearance were immersed in boiling water for 24 hours as a boiling water resistance test, and then heated again at 300°C for 60 minutes and observed for appearance. The results are shown in Table 1, and those that were not suitable were treated as comparative examples. From the results in Table 1, it was considered that the appropriate coating amount of ZrO2 was 10 to 2000mg / m2, and more preferably 100 to 1000mg / m2. [Table 1]
[0026] "Examples 6 to 11, Comparative Examples 3 to 4" Here, we fixed the amount of ZrO2 applied and investigated the protection of the pattern when the amount of SiO2 applied was gradually changed. A 10cm x 10cm iron plate was heated in an oven at 300°C for 60 minutes to color it bluish black. A pattern was drawn on the surface of this iron plate by scraping it with a file. The scraped parts were the original silver color of the iron plate, so a silver pattern was drawn against a black background. The ratio of scraped parts was arbitrary. Ammonium zirconium carbonate (ZrO2 content 20wt%) was diluted with distilled water to prepare a coating solution with ZrO2 = 5wt%. 0.1g of each coating solution was dropped onto the iron plate surface (area 0.01m2) and spread evenly over the entire surface. The coating amount ratio was 500mg / m2 in terms of ZrO2. This was dried at 100°C for 5 minutes. Next, an aqueous solution of lithium-containing alkali silicate with a composition of SiO2=10, Li2O=0.3, and Na2O=1.7wt% was prepared, and 0, 0.01, 0.05, 0.1, 0.2, 0.3, and 0.4g were dropped onto the iron plate coated with the above-mentioned ammonium zirconium carbonate, and the solution was spread evenly over the entire surface. The coating amount ratios of these are 0, 100, 500, 1000, 2000, 3000, and 4000mg / m2, respectively, in terms of SiO2. This was heated in an oven at 300°C for 60 minutes. After observing the appearance after heating, the plate was immersed in boiling water for 24 hours, and then heated again at 300°C for 60 minutes, and the appearance was observed. From the results in Table 2, it was considered that the appropriate coating amount of SiO2 is 100 to 3000mg / m2, and the more suitable coating amount is 100 to 2000mg / m2. [Table 2]
[0027] "Example 12, Comparative Example 5" Here, the stability of the coating solution was examined. First, an aqueous solution of ammonium zirconium carbonate (concentration of 5 wt% in terms of ZrO2) was prepared. An aqueous solution of an alkali silicate containing lithium (equivalent contents of SiO2 = 10 wt%, Li2O = 0.3 wt%, Na2O = 1.7 wt%) was also prepared. Neither solution was stored at room temperature for six months, and no problems of precipitation or gelation occurred. When the two were mixed in a weight ratio of 9:1 or 5:5, respectively, the former gelled after 24 hours, and the latter after 10 minutes. The former could be coated if painted quickly, but the latter was not. 0.1 g of the ammonium zirconium carbonate solution and the 9:1 mixture were dropped onto a 10x10cm iron plate with a pattern drawn in the same manner as in Example 9, spread over the entire surface, and dried at 60°C for 5 minutes. Furthermore, 0.1 g of the lithium-containing alkali silicate aqueous solution was dropped onto the surface, spread over the entire surface, and heated at 300°C for 10 minutes to obtain iron plates with the patterns of Example 12 (first layer ZrO2 alone) and Comparative Example 5 (first layer ZrO2 and SiO2 mixed). No discoloration of the pattern or peeling of the coating was observed after heating in either case. Each iron plate was immersed in boiling water for 24 hours and then heated at 300°C for 60 minutes. In Example 9, no abnormality was observed in the pattern, but in Comparative Example 5, the silver part of the pattern turned black, making it difficult to see the pattern. These differences are due to whether the coating solution for the first layer contains silicon or not, and it is believed that the silicon compound reacts chemically with the ammonium zirconium carbonate in the coating solution, causing gelation to progress and weakening the coating film, even if the coating work can be done. It cannot be said that mixing ammonium zirconium carbonate and a silicon compound and coating it is suitable for protecting the pattern.
[0028] "Examples 13-14, Comparative Examples 6-7" Here, the presence or absence of lithium in the second coating layer was examined. An aqueous solution of ammonium zirconium carbonate (concentration 5% in terms of ZrO2) was prepared as the first coating solution. 0.1 g of this solution was dropped onto a 10x10 cm iron plate similar to that in Example 9, spread over the entire surface, and dried at 60°C for 5 minutes. Next, an aqueous solution of alkali silicate with a stepwise change in lithium content was prepared, and 0.1 g was dropped onto the iron plate coated with the aqueous solution of ammonium zirconium carbonate, spread over the entire surface, and then heated at 300°C for 10 minutes. After observing the appearance of the iron plate thus obtained, it was immersed in boiling water for 24 hours, and further heated at 300°C for 60 minutes to observe the appearance. These results are summarized in Table 3. As shown in Table 3, when Li2O was not included, SiO2 disappeared due to boiling water, and the pattern turned black due to heating, making the difference from the surroundings unclear. In addition, when Li2O was excessive, the coating layer turned white at the time of baking the second layer, which was not suitable. [Table 3]
[0029] "Examples 15 to 20 and Comparative Examples 8 to 13" Here, the appropriate solid concentration range of the second coating layer components was examined. A coating solution was prepared using lithium silicate, sodium silicate, potassium silicate, sodium hydroxide, lithium hydroxide, and potassium hydroxide to obtain the composition shown in Table 4. A pattern was created on the iron plate in the same manner as in Example 9, and ammonium zirconium carbonate was applied to this to a ZrO2 equivalent value of 500 mg / m2, and dried at 60°C. A coating solution having the composition shown in Table 4 as the second layer was applied to these iron plates to a SiO2 equivalent value of 1000 mg / m2, and baked and dried at 300°C for 10 minutes. After observing the appearance of this, it was immersed in boiling water for 24 hours and then heated at 300°C for 60 minutes to observe the state of the pattern. From the results in Table 4, the appropriate composition of the second coating layer is in the range of SiO2 = 70 to 90 wt%, and if it is less than this, it will dissolve in boiling water, and when reheated, the pattern will blacken and become the same color as the surroundings and disappear. Also, if it is more than this, whitening was observed during baking. The appropriate amount of Li2O was 1-5wt%, and it was found that if it was insufficient, the coating layer would dissolve, and if it was excessive, it would turn white. As for Na2O and K2O, if SiO2 and Li2O were appropriate, it was thought that the appropriate amount for the remaining components would be 5-29wt%. [Table 4]
[0030] "Example 21" In Example 21, the masking method was used for imaging. A commercially available iron frying pan was purchased, and the surface treatment layer was polished off to expose the silvery iron. A drawing was then made on the cooking surface of this surface using No. 3 sodium silicate, and this was then dried. Next, this frying pan was heated to 400°C for 10 minutes, and the parts covered with No. 3 sodium silicate were masked and did not blacken due to heating, so the drawn parts turned silver and the undrawn parts turned black, resulting in an iron frying pan with a clearly drawn pattern. The frying pan was then immersed in boiling 1% sodium hydroxide solution for 2 hours to dissolve and remove the sodium silicate masking. It is well known that solidified sodium silicate dissolves in boiling water or alkaline boiling water. Even after this dissolution and removal process, the black parts do not dissolve, so the pattern remains. The surface of this pattern was coated with an alkali silicate containing ammonium zirconium carbonate and lithium under the same conditions as in Example 9, and baked to obtain an iron frying pan usable for cooking as Example 21. It was confirmed that the pattern remained the same as when it was first used, even after one year of actual use, and the pattern was preserved.
[0031] "Example 22" A commercially available iron frying pan was purchased, and the surface treatment layer was polished off to expose the silvery iron. A pattern was drawn on the cooking surface with an aqueous solution of ammonium zirconium carbonate with a concentration of 1% in terms of ZrO2 and then dried. The frying pan was then heated at 400°C for 30 minutes, and the parts not covered with the aqueous solution of ammonium zirconium carbonate were colored black, while the parts covered with the aqueous solution were colored blue because oxidation was partially suppressed by masking. The pattern was drawn with this black and blue coloring. The layer of the coating masked with ammonium zirconium carbonate becomes zirconium oxide, so there is no need to remove it and it can be used as it is as the first layer. The blue part has a double layer of zirconium oxide, but this is not a problem. The surface of this pattern was coated with an alkali silicate containing ammonium zirconium carbonate and lithium under the same conditions as in Example 9, and baked to obtain an iron frying pan usable for cooking as Example 22. Even after one year of actual use, this pattern remained the same as the initial pattern.
[0032] "Examples 23 and 24" A commercially available cast iron frying pan was prepared. The surface of this frying pan was rough and porous, so it was water-absorbent. It was polished until it turned silver, but water absorption was still observed. This frying pan was heated to 400°C and colored black. When it was immersed in an aqueous solution of ammonium zirconium carbonate with a ZrO2 concentration of 4%, the liquid was thoroughly shaken off, and then it was dried, a coating defect was observed in which white powder was generated. When the same treatment was performed on a frying pan made of rolled steel plate, the problem of white powder generation was not observed. This was thought to be because cast iron is water-absorbent, so it absorbs a lot of the coating liquid, and the amount of zirconium oxide applied was too large. Therefore, in order to reduce the water absorption rate, an aqueous solution of lithium-containing alkali silicate with a composition of SiO2=10, Li2O=0.3, Na2O=1.7wt% was prepared, and the same frying pan as before before immersing it in the aqueous solution of ammonium zirconium carbonate was immersed in this solution, and the liquid was drained and dried, but the generation of white powder was not observed. The aqueous solution of alkaline silicate is a glassy substance also known as water glass, and is less likely to be powdered than zirconium oxide, so it was thought that the sealing was successful. Next, when this sealed product was immersed in the aqueous solution of ammonium zirconium carbonate with a ZrO2 concentration of 4%, no problem of white powder generation was observed, as with the frying pan made of rolled steel plate. Furthermore, these sealed products and the frying pan made of rolled steel plate were each immersed in the aqueous solution of alkaline silicate containing lithium, drained, and further heated at 300°C for 30 minutes to obtain iron products usable for cooking in Examples 23 and 24, respectively. In practical use, no inconvenience such as white powder generation was observed. The commercially available iron frying pans shown in the examples before Example 24 are made of rolled steel plate.
[0033] "Example 25" The frying pan made of rolled steel plate obtained in Example 24 was immersed in an aqueous solution of zirconium carbonate with a ZrO2 concentration of 4%, drained, and dried at 300°C for 30 minutes to obtain the iron product usable for cooking in Example 25. The surface had a pearl-like luster due to the high refractive index of zirconium oxide, but no problems such as whitening or white powder generation occurred. When comparing the frying pans of Examples 24 and 25, it was found that the former was easier to remove oil stains and the latter was easier to remove burnt stains than the other. It was considered appropriate to use them depending on the type of cooking.
[0034] "Example 26" As in Example 21, a commercially available iron frying pan was purchased, and the surface treatment layer was polished off to expose the silvery iron. This surface was then painted with an aqueous solution of alkaline silicate containing lithium with a composition of SiO2=10, Li2O=0.3, and Na2O=1.7wt%, and dried. Next, this frying pan was heated at 400°C for 10 minutes, and the parts covered with the aqueous solution of alkaline silicate were masked and did not blacken due to heating, so the painted parts were silver and the unpainted parts were black, resulting in an iron frying pan with a clear pattern. In Example 21, the masking was removed with boiling water, but in Example 26, it was not removed, and an alkaline silicate containing ammonium zirconium carbonate and lithium was applied to the surface of the pattern under the same conditions as in Example 9, and baked to obtain an iron frying pan usable for cooking in Example 26. It was confirmed that the pattern remained the same as when it was first used, even after one year of actual use, and the pattern was protected. [Industrial Applicability]
[0035] The iron products with the patterns obtained by this invention do not lose their patterns even when exposed to high temperatures and boiling water for long periods of time. They are resistant to rust, food does not stick to them, and are easy to clean. Therefore, they can be used for cooking utensils, and it has become possible to further improve the design. [Explanation of symbols]
[0036] 100: Iron plate 120: Parts discolored by oxidation 110: Glassy layer containing silicon (no need to cover the entire surface) 130: Zirconium oxide layer 140: Transparent lithium-containing alkali silicate layer 150: Adhesion interface between 1st and 2nd layers 160: Adhesion interface between the second and third layers 200: Iron plate 220: Parts discolored by oxidation 210: Glassy layer containing silicon (no need to cover the entire surface) 230: transparent zirconium oxide layer 240: Transparent lithium-containing alkali silicate layer 250: transparent zirconium oxide layer
Claims
1. The iron product usable for cooking has a surface covered with a transparent zirconium oxide layer and is further covered with a transparent lithium-containing alkali silicate layer, the zirconium oxide layer having a ZrO2 equivalent value of 10 to 2000 mg / m2, the lithium-containing alkali silicate layer having a silicon content of 10 to 3000 mg / m2 in SiO2 equivalent value, and a chemical composition of SiO2 = 70 to 90 wt%, Li2O = 1 to 5 wt%, Na2O + KO = 5 to 29 wt%.
2. The iron product according to claim 1, wherein the surface of the iron product usable for cooking is further coated with a transparent zirconium oxide layer, and the zirconium oxide layer has a ZrO2 equivalent value of 10 to 2000 mg / m2.
3. 2. The iron product usable for cooking according to claim 1, characterized in that a part or all of the iron surface beneath the coating layer is coated with a silicon-containing glass material.
4. The iron product according to claim 1, which can be used for cooking, has a part or the whole of the iron surface under the coating layer that is colored by a chemical reaction due to oxidation.
Citation Information
Patent Citations
JP1975144639A
Solution composition of metal surface-treatment agent containing zirconium as main component, and surface-treatment method
JP2009041077A
